An environment-friendly and multi-functional absorbent from chitosan for organic pollutants and heavy metal ion. (5th September 2016) - Li, Ang; Lin, Runjun; Lin, Chong; He, Bianyang; Zheng, Tingting; Lu, Lingbin; Cao, Yang
Highlights: Chitosan aerogel was fabricated in a simple method involving a cross-linked process and freeze drying technique. The aerogel performed higher adsorption capacity for organic pollutants and heavy metal ion. The high versatile adsorptivity and good elastic resilience endowed the absorbent with a more flexible and convenient application mode. Abstract: Developing environment-friendly green absorbents for disposal of wastewater remains to be studied. In this paper, the cross-linked chitosan aerogel (CsA) as an environment-friendly absorbent was obtained by a simple method involving cross-linked process and freeze drying technique. Compared with conventional absorbents, the porous chitosan aerogel was provided with unique properties such as low density (0.0283 g/cm 3 ), high porosity (97.98%) and outstanding adsorption performance. The chitosan aerogel also displayed good reusability and excellent elasticity with a maximal thickness recovery up to 96.8% of the original thickness. The as-prepared absorbent exhibited preferable adsorption capacities for crude oil, diesel and copper ion (41.07 g/g, 31.07 g/g and 21.38 mg/g, respectively). The aerogel can collect a wide range of organic solvents and oils with absorption capacities up to 40 times their own weight, depending on the density and viscosity of the liquids. The adsorption capacity for heavy metal ion was also considerable and the maximum adsorption capacity ( q m ) of the aerogel for copper ion was 35.08 mg/g according to Langmuir isotherm model. Consequently, the chitosan aerogel with versatile adsorption properties has a good potential for wastewater treatment in environmental application.